Lower hypoxic ventilatory response in smokers compared to non-smokers during abstinence from cigarettes - Hildebrandt, Wulf; Sauer, Roland; Koehler, Ulrich; Bärtsch, Peter; Kinscherf, Ralf (BMC pulmonary medicine, 2016)
Carotid body O2-chemosensitivity determines the hypoxic ventilatory response (HVR) as part of crucial regulatory reflex within oxygen homeostasis. Nicotine has been suggested to attenuate HVR in neonates of smoking mothers. However, whether smoking affects HVR in adulthood has remained unclear and probably blurred by acute ventilatory stimulation through cigarette smoke. We hypothesized that HVR is substantially reduced in smokers when studied after an overnight abstinence from cigarettes i.e. after nicotine elimination.
Gesehen am 13.05.2020